Repurposing riluzole as an anti-osteosarcoma agent - Jung, Okkeun; Rajasekhar, Vinagolu K.; Azeem, Syeda Maryam; ChandThakuri, Shraddha; Norton, Beatrice; Healey, John H.; Mahajan, Shahana (Frontiers in Oncology, 2025)
We have studied riluzole, a glutamate-release inhibitor, as a novel anti-osteosarcoma agent. YAP (Yes-associated protein) is recruited by Bax promoter to stimulate its expression during riluzole-induced apoptosis in the human metastatic osteosarcoma cell line LM7. Given the substantial genetic heterogeneity in osteosarcoma, studies on the efficacy of riluzole in diverse osteosarcomas will be an asset in developing preclinical studies. Toward this goal, we investigated the effects of riluzole on 11 osteosarcoma cell lines derived from primary or metastatic tumors of mouse or human origin and on four independent patient-derived xenograft (PDX) tumor cell lines. We found that most of the osteosarcoma cell lines, including PDX cell lines secrete glutamate and exhibit invasive abilities. Cell growth and invasive ability of all the cell lines and PDX cell lines are inhibited by riluzole. Additionally, riluzole suppresses the activity of matrix metalloprotease-2 (MMP2) in most of the osteosarcoma cell lines (but not the PDX cells). These results suggest that riluzole’s inhibitory effects on osteosarcoma invasion may in part be attributable to the inhibition of MMP2 activity, and that riluzole is potentially an effective agent for inhibiting growth of primary and metastatic osteosarcomas with a wide range of genetic profiles.